Capitalism and Class in the Gulf Arab States : By Adam Hanieh (New York: Palgrave Macmillan, 2011. 266 pages.) (American Journal of Islam and Society, 2013)
To label Adam Hanieh’s Capitalism and Class in the Gulf Arab States an afterstudyof the 2008 financial crisis is a grossly unfair assessment. While thebook does explore the implications of the Gulf states’ financial slump, it alsoprovides a nuanced analysis of their class structures and relation to the globalcapital system. The exponential growth of the Gulf Cooperation Council(GCC) states is the book’s main subject; however, Hanieh dexterously avoidsthe common errors involved in the region’s economic analysis and thus addsto the corpus of literature pertaining to both the GCC and the wider globaleconomy.The class structures and wealth prevailing in the GCC are often seen asan outcome of the states being oil rich. Hanieh problematizes this narrativeby positing that this wealth and structuring is not “accidental” and that whileoil is undeniably important, it is not the sole reason for the region’s situation.He urges the reader to look beyond the hydrocarbon wealth, because “muchlike its desert cousin, the mirage – what visitors actually see in the oil-fueledboom is not the full picture” (p. 2).Hanieh’s choice of viewing the GCC holistically, instead of addressingspecific nation-states, is significant. The “internationalization” of the localeconomy and class structure results in the dissolution of class boundariesamong the states and paves the way for capitalism. But at the same time, however,capitalism needs to be valorized in a coherent and material time andspace. This valorization has taken the special form of the regional GCC andbecomes the study’s focal point. This regionalization has displaced “powerupwards to the regional scale, weakening the ability of the individual memberstates to control the movement of goods and capital within the intra-GCCspace” (p. 104).The author also problematizes the “rentier-state” theory through a Marxianframework. He urges the reader not to consider the state, and particularlythe states of the Gulf nations, as a “thing” or an automatic reflection of thecapitalist class, but rather as “a particular expression of class formation” (p.12). This also implies that the state has greatly facilitated the development ofthe GCC’s prevailing “hot-house” economy (p. 15).The study’s regional nature culminates in the analysis of “Khaliji” capital.In the Gulf states, the internationalization of capital manifests itself in aregional form as the “circuits of capital are themselves elaborated at the ...